Memory and likeness of Fulbert Youlou (1947-1963) - Zéphirin Sah; Raymond Menga-Poaty (International Journal of Social Service and Research (IJSSR), 2023)
Under the colonial period, certain leaders of sub-Saharan Africa having received intellectual training gradually asserted themselves in the political arena. Among this elite, one of the emblematic figures is Abbé Fulbert Youlou, one of the fathers of the independence of the Congo between 1960 and 1963. He belongs to the Kongo ethnic group whose members were under French colonization, the head poster of the intellectual elite known as "the evolved" prepared to succeed the colonizer. This study displays the portrait of this character who marked the history of the young Republic of Congo. The duty of remembrance demands it from us especially on the eve of the celebrations linked to the 60 years of independence of the Congo.